2015
DOI: 10.1016/j.bone.2015.07.011
|View full text |Cite
|
Sign up to set email alerts
|

Influence of vitamin D and estrogen receptor gene polymorphisms on calcium absorption: Bsm I predicts a greater decrease during energy restriction

Abstract: Low calcium absorption is associated with low bone mass and fracture. In this study, we use gold standard methods of fractional calcium absorption (FCA) to determine whether polymorphisms of intestinal receptors, vitamin D receptor (VDR) and estrogen receptor α (ESR1), influence the response to energy restriction. Fractional calcium absorption was measured using dual stable isotopes (42Ca and 43Ca) in women given adequate calcium and vitamin D and examined at baseline and after 6 weeks of energy restriction or… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 47 publications
0
6
0
Order By: Relevance
“…However, the author proposed that further studies with larger sample sizes from wider geographical areas are required for validation. Recently, Chang et al (2015) reported the Bsm I polymorphism in intestinal VDR may contribute to alterations in bone health. There is new evidence regarding the role of CD40 and CDL40 systems in the homeostasis of bone marrow cells.…”
Section: Major Biological Pathways Involved In Osteogenesis Related Tmentioning
confidence: 99%
“…However, the author proposed that further studies with larger sample sizes from wider geographical areas are required for validation. Recently, Chang et al (2015) reported the Bsm I polymorphism in intestinal VDR may contribute to alterations in bone health. There is new evidence regarding the role of CD40 and CDL40 systems in the homeostasis of bone marrow cells.…”
Section: Major Biological Pathways Involved In Osteogenesis Related Tmentioning
confidence: 99%
“…Mechanistically, Arai et al [13] showed that the A allele of Cdx2 has a higher transcriptional activity of VDR than the G allele in vitro. To our knowledge, however, there is no experimental study investigating whether the Cdx2 polymorphism affects calcium absorption, despite it having been investigated for other VDR polymorphisms (BsmI, TaqI, and ApaI) using dual stable isotopes [45,46]. It was reported that the Cdx2 polymorphism modified the positive association between calcium intake and prostate cancer risk in White [47] and African American [48] people.…”
Section: Discussionmentioning
confidence: 99%
“…The reason for this may be associated with VDR signal enhancement although we could not identify the specific underlying mechanism. Additionally, previous studies demonstrated that VDR polymorphism is associated with calcium absorption 24 ) . Taking these facts into account, we speculate that one explanation for the characteristics of our new CKD model is susceptibility to VDRA due to VDR gene polymorphism.…”
Section: Discussionmentioning
confidence: 99%